O efeito das escolas federais sobre o desempenho no ENEM 2020 e a igualdade de oportunidades no acesso a esse tipo de ecola: análise comparativa para o estado do Ceará. - Sousa, Larissa Mota de (2022)
The present research aims to analyze the share of the effect of federal schools on the results of ENEM 2020 on the difference in scores between students of this type of school in Ceará and those from state schools and to investigate whether there is inequality of opportunity in access to these federal schools. For this, the propensity score matching method (PSM) is used to compare the performances of the two mentioned groups, based on a probit regression that estimates which characteristics affect the probability of studying in a federal school. Furthermore, the Gini Index, the Dissimilarity Index (ID) and the Human Opportunity Index (HOI) are calculated to measure the inequality of opportunities in accessing federal schools. The final sample, after applying all the filters, consists of 1.312 students who completed high school in the public network in 2020 in the state of Ceará and who did not present any omitted variable.Regarding the results, after controlling for ethnic, demographic and family background variables, it can be said that students from federal schools present better results in all ENEM areas in Ceará and that the inequality of opportunities in access to this type of school it is very small.